1978
DOI: 10.1002/jpln.19781410113
|View full text |Cite
|
Sign up to set email alerts
|

N2‐Fixation by roots and rhizosphere of sand dune plants

Abstract: Nitrogenase activity (by acetylene reduction assay) has been found on the roots and in the rhizosphere‐soil of various plant species collected from dune soils (Table 1.) located on the west coast of Denmark. Out of twelve plant species, five plant species (Deschampsia flexuosa, Ammophila arenaria, Calluna vulgaris, Empetrum nigrum and Corynephorus canescens) revealed a positive nitrogenase activity. Among these five, three were temperate grasses. Except Ammophila arenaria, all four plant species were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…have been reported for Ammophila arenaria grown in dune sand with an exogenous carbon (C) source (1). Either low (2,28) or high (R. Ralph, Ph.D. dissertation, University of Delaware, Newark, 1978) rhizosphere nitrogenase activity has been reported for several grasses growing in unamended sand. Significant enhancement of growth, but not of plant-N content, often occurs following root inoculation with asymbiotic N2-fixing bacteria (14,18,22).…”
mentioning
confidence: 99%
“…have been reported for Ammophila arenaria grown in dune sand with an exogenous carbon (C) source (1). Either low (2,28) or high (R. Ralph, Ph.D. dissertation, University of Delaware, Newark, 1978) rhizosphere nitrogenase activity has been reported for several grasses growing in unamended sand. Significant enhancement of growth, but not of plant-N content, often occurs following root inoculation with asymbiotic N2-fixing bacteria (14,18,22).…”
mentioning
confidence: 99%
“…Highest activities were found with roots of 3 grass species from sandy soil low in COrg. Similarly, Ammophila arenaria, Deschampsia flexuosa and Corynephorus canescens from Danish coastal dunes had a high activity of 260,respectively (Ahmad and Neckelmann, 1978). A consistently high activity as with Tussilago farfara was found also with roots of other Asteraceae (Cichorium intybus, Helianthus annuus, Dahlia veriabilis and Taraxacum officinale) with inuline as storage material (Vlassak and Jain, 1978).…”
Section: Diecussionmentioning
confidence: 93%
“…Nitrogenase activity associated with plant roots was measured by the acetylene reduction technique not only in the tropics, but also with numerous wild plants ( Tjepkema and Evans, 1976,Ahmad and Neckelmann, 1978, Kana and Tjepkema, 1978 and cereals of temperate climates ( P e a h e n et al, 1978). It increases with the rate of photosynthesis, soil moisture and soil temperature, but is diminished with increasing Nmin contents of soils ( Balandreau et al 1978), Dobereiner and De-Polli, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Using the acetylene reduction test (Dilworth 1966, Hardy et al 1972) significant nitrogenase activities of grass roots were observed after induction by preincubation of washed roots under atmospheres of reduced oxygen tension (Dobereiner et al 1972, Domrnergues et al 1972, Neves et al 1973, Dayet al 1975, Dobereiner and Day 1975, Ahmad and Neckelmann 1978). However, this preincubation for 12 hours with 1-2 % O2 caused a considerably enlarged population of Spirillum lipoferum as a result of the organic acids formed by the roots and other associated microorganisms leading to acetylene reduction rates an order of magnitude higher than with roots left in soil core samples .…”
Section: Nitrogen Fixation In the Rhizosphere Of Grasses And Cerealsmentioning
confidence: 99%